Pengembangan Media Interaktif Tata Surya Pada Pembelajaran Untuk Meningkatkan Hasil Belajar IPA Kelas VI SDN 1 Gunung Terang - Connyta Elvadola; Ridho Agung Juwantara; Try Indiastuti Kurniasih; Amilia Rasitiani (Program Studi PGSD, Jurusan Ilmu Pendidikan, STKIP PGRI Bandar Lampung, 2023)
The purpose of this study was to determine the effectiveness of developing interactive media on solar system material in improving student learning outcomes. The method used is the Research and Development method (research and development). The stages of development in this study began with analyzing needs, designing, making interactive media, then applying it in learning and then testing student learning outcomes. Data analysis was carried out using descriptive percentages and one sample test for student completeness. This can be seen from the validation results of material experts who stated